Revisiting pulmonary fibrosis: inflammatory dynamics of the lipofibroblast-to-inflammatory lipofibroblast-to-activated myofibroblast reversible switch - Panagiotidis, Georgios-Dimitrios; Vasquez-Pacheco, Esmeralda; Chu, Xuran; Seeger, Werner; El Agha, Elie; Bellusci, Saverio; Lingampally, Arun; Justus Liebig University Giessen (My University, 2025)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease characterized by excessive extracellular matrix (ECM) deposition and irreversible lung damage. A key driver of disease progression is the phenotypic shift of lipofibroblasts (LIFs) into activated myofibroblasts (aMYFs), triggered by sustained epithelial injury, caused by inflammation, oxidative stress, viral infections (e.g., influenza, SARS-CoV-2), and metabolic dysfunction. Emerging evidence demonstrates that this transition is reversible, with pharmacological agents that promote aMYF-to-LIF reprogramming contributing to fibrosis resolution. The identification of inflammatory lipofibroblasts (iLIFs) Highlights the importance of inflammation in fibrosis progression. Inflammation, mediated by IL-1b, IL-17A, and TGF- b, sustain aMYF activation, while immune cells shape fibrosis formation. This review combines current insights on the cellular and molecular pathways controlling fibroblast differentiation, highlighting key metabolic, immunologic, and oxidative stress-modulating targets for therapeutic intervention. Understanding and manipulating the LIF-iLIF-aMYF axis offers a promising strategy for reversing fibrosis and restoring pulmonary homeostasis in IPF
Keywords: ddc:610